Bibliometric Analysis of Global Pediatric Research on Cow‘s Milk Protein Allergy - Lin X; Chen Y; Lin W (Journal of Asthma and Allergy)
Xiaolan Lin,1,* Yifan Chen,2,3,* Weidong Lin1 1Department of Pediatric Gastroenterology, Fuzhou Children’s Hospital of Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 2Shengli Clinical Medical College, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 3Department of Gastrointestinal Surgery, Fujian Provincial Hospital, Fuzhou, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weidong Lin; Yifan Chen, Email lwd@fjmu.edu.cn; 597039383@qq.comBackground: Cow’s milk protein allergy (CMPA) is a prevalent food allergy in early childhood, significantly impacting the quality of life for affected children. Current palliative measures, such as specialized formula milk, offer temporary relief but are costly and fail to address the underlying issue. Thus, there is a critical need to better understand CMPA and explore new treatment options.Methods: This study employed bibliometric methods to analyze global pediatric CMPA research and identify future directions for the first time. Visual analyses were conducted using VOS Viewer and CiteSpace software.Results: A total of 2040 articles published between 2000 and 2023 showed increasing annual publications. In this field of research, the Icahn School of Medicine at Mount Sinai has made significant contributions, with the most influential articles published in the Journal of Allergy and Clinical Immunology. Current research emphasizes personalized therapy, probiotics, and gut microbiota in CMPA.Conclusion: Future research will focus on microbiota-related personalized treatments, promising effective clinical interventions.Keywords: Pediatric, Cow’s milk protein allergy, Bibliometric analysis, Gut microbiota